2008
DOI: 10.1152/ajplung.90204.2008
|View full text |Cite
|
Sign up to set email alerts
|

Induction of IL-8 byMycoplasma pneumoniaemembrane in BEAS-2B cells

Abstract: Mycoplasma pne umoniae is an extracellular pathogen, residing on mucosal surfaces of the respiratory and genital tracts. The lack of cell walls in mycoplasmas facilitates the direct contact of the bacterial membrane with the host cell. The cell membrane of mycoplasma is the major inducer of the host pathogenic response. Airway diseases caused by M. pneumoniae include bronchiolitis, bronchitis, and rarely bronchiectasis. In such disorders, neutrophil infiltration of the airways predominates. More recently, M. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 73 publications
(77 reference statements)
1
37
0
1
Order By: Relevance
“…Previous reports showed that live M. pneumoniae infection induces IL-8 expression from human lung epithelial cells and macrophages. Additionally, our recent study showed that M. pneumoniae membrane and LPP induced IL-8 production from BEAS-2B cells and that NF-B and to a lesser extent the MAPK pathways played an important role in the induction (14).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous reports showed that live M. pneumoniae infection induces IL-8 expression from human lung epithelial cells and macrophages. Additionally, our recent study showed that M. pneumoniae membrane and LPP induced IL-8 production from BEAS-2B cells and that NF-B and to a lesser extent the MAPK pathways played an important role in the induction (14).…”
Section: Discussionmentioning
confidence: 93%
“…Although M. pneumoniae is a well established cause of asthma exacerbations, more recent data have suggested that it may also contribute to the pathogenesis of asthma (7)(8)(9)(10)(11)(12). The lipoprotein constituents of M. pneumoniae membrane play a critical role in immune recognition by the host and induction of the inflammatory response (13,14). The membrane components are recognized mainly by the Toll-like receptors, TLR1, 2 TLR2, and TLR6, that initiate downstream signaling events including activation of NF-B and the mitogen-activated protein kinases (MAPKs) (15).…”
mentioning
confidence: 99%
“…Interleulin-8 is an inflammatory cytokine and functions as an activator of neutrophils. Several lines of recent in-vitro evidence have supported the pathogenic importance of interleukin-8 in the development of the clinical picture of M. pneumoniae respiratory infection [Chmura et al, 2008;Sohn et al, 2005;Yang et al, 2002]. From this perspective, the activation of interleukin-8 by M. pneumoniae is one of the key steps in inducing the vasculitic disorders which are the main subject of this chapter.…”
Section: Wwwintechopencommentioning
confidence: 90%
“…Several membrane proteins in M. pneumoniae have high affinity for various surface receptors on host cells [77]. Through interaction with recognition receptors, including toll-like receptors 2 and 6, mycoplasma membrane lipoproteins are able to induce host immune responses [77,78]. Adherence of M. pneumoniae to host cells in the respiratory tract is mediated by the P1 adhesin protein and accessory proteins [79][80][81][82].…”
Section: Clinical Aspects Of ML R M Pneumoniae Infectionmentioning
confidence: 99%
“…ML possess antimicrobial activity against M. pneumoniae, and also have anti-inflammatory effects. For example, CAM is able to suppress IL-8 induction, even in ML r M. pneumoniae infection [78,86,90]. Thus, clinical efficacy of ML in treating M. pneumoniae infection may reflect not only direct antimicrobial activity but also anti-inflammatory effects of inhibition of production of cytokines, including IL-8.…”
Section: Clinical Aspects Of ML R M Pneumoniae Infectionmentioning
confidence: 99%